(untitled) (Culturas Científicas, 2025)
The development of Cognitive Ethology has given rise, since its beginnings, to a series of debates about the possible anthropomorphism that could be implied in theorizations about the animal mind. However, if one examines carefully the way in which contemporary studies on animal cognition are actually formulated, designed and developed, one notices that this concern is, to a large extent, impertinent or at least exaggerated. Moreover, it can be concluded that this concern has often been motivated more by a deficient or misleading understanding of the concept of the mental, than by aspects inherent to the concrete way in which such research is carried out. In this sense, if one adopts the conception of mental predicates formulated by Gilbert Ryle, and keeps in focus the way in which these predicates are effectively used in empirical studies on animal cognition, anthropomorphism can be considered as a legitimate heuristic resource, always subject to objective controls. In fact, if there is a relevant obstacle in these investigations, it lies less in anthropomorphism than in an anthropocentric bias. The articulation between cognitive parsimony, proposed by Morgans Canon, and evolutionary parsimony define the royal road to circumvent this bias.